Effects of olive leaf extract (oleuropein) on performance, fatty acid levels of breast muscle and some blood parameters in Japanese quail (Coturnix coturnix Japonica) reared in different stocking densities - Bahsi, Muammer; Ciftci, Mehmet; Simsek, Ulku Gulcihan; Azman, Mehmet Ali; Ozdemir, Gokce; Yilmaz, Okkes; Dalkilic, Bestami (Ankara Univ Press, 2016)
This study was performed to determine the effects of olive leaf extract (oleuropein) on performance, fatty acid levels of breast muscle and some blood parameters in quails reared in different stocking densities. In the study, a total of 270 quail chicks (Coturnix coturnix Japanica), 15 days-old were used. The birds were randomly assigned according to 2 stocking densities (12, 18 birds/cage) x 3 oleuropein levels (0, 200, 400 ppm) including 6 treatment groups of 3 replicates while keeping the gender (135 female, 135 male) and initial weight balanced. The treatment was completed until 29 days. Stocking densities were arranged to be 100 and 150 cm(2) per quail in cages. Higher stocking density negatively affected live weight, body weight gain and carcass parameters (P<0.05). Oleuropein which added to mixed feed increased body weight gain, polyunsaturated fatty acid ratio, omega 3 and 6 fatty acid levels of breast muscle, and improved feed conversion rate (P<0.05) while reducing saturated fatty acid level of breast muscle (P<0.05). Consequently, dietary oleuropein supplementation would improve performance and quality of breast muscle lipids by lowering saturated fatty acid proportions and by enhancing contents of polyunsaturated fatty acids in either stocking densities. According to examined parameters, a dose of 400 ppm oleuropein provided preferable results among the groups, especially in higher stocking density.
Farklı yerleşim sıklığında yetiştirilen Japon bıldırcınlarında (Coturnix coturnix Japonica) zeytin yaprağı ekstraktının (oleuropein) performans, göğüs eti yağ asidi düzeyleri ve bazı kan parametrelerine etkisi
Keywords: Carcass lipids; olive leaf extract; performance; quail; stocking density